2015
DOI: 10.1093/pcp/pcv076
|View full text |Cite
|
Sign up to set email alerts
|

SNARE Molecules inMarchantia polymorpha: Unique and Conserved Features of the Membrane Fusion Machinery

Abstract: The membrane trafficking pathway has been diversified in a specific way for each eukaryotic lineage, probably to fulfill specific functions in the organisms. In green plants, comparative genomics has supported the possibility that terrestrialization and/or multicellularization could be associated with the elaboration and diversification of membrane trafficking pathways, which have been accomplished by an expansion of the numbers of genes required for machinery components of membrane trafficking, including solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 125 publications
2
116
0
Order By: Relevance
“…To test the hypothesis that core PTB proteins traffic to the plasma membrane through the secretory pathway, we expressed an MpPTB6‐YFP fusion protein in M. polymorpha . YFP fluorescence location was identical to that of the plasma membrane marker mCitrine‐MpSYP12A (Kanazawa et al ., ) and the ER marker YFP‐HDEL (Teh & Moore, ) in 25% and 75%, respectively, of plants expressing MpPTB6‐YFP (Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…To test the hypothesis that core PTB proteins traffic to the plasma membrane through the secretory pathway, we expressed an MpPTB6‐YFP fusion protein in M. polymorpha . YFP fluorescence location was identical to that of the plasma membrane marker mCitrine‐MpSYP12A (Kanazawa et al ., ) and the ER marker YFP‐HDEL (Teh & Moore, ) in 25% and 75%, respectively, of plants expressing MpPTB6‐YFP (Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…Distinct from the other MpSYP1 members, MpSYP12B exhibits specific expression in oil body cells and localizes to the oil body membrane 10 . Oil body cells expressing a pro Mp SYP12B: 2×YFP construct indicated that MpSYP12B distributed around meristematic regions in young thalli, which was observed using light-sheet microscopy (Fig.…”
Section: Main Textmentioning
confidence: 98%
“…About 90% of liverwort species have this organelle; however, its origin, biogenesis, and physiological function remain unclear with controversial origins proposed from microscopic observations 69 . Through the systematic analysis of SNARE proteins in the liverwort, Marchantia polymorpha (hereafter referred to as Marchantia), we identified an oil body-resident protein, MpSYP12B 10 , which is a homolog of animal Syntaxin 1 that acts in the final step of exocytosis. Functions of SYP1 members to which MpSYP12B belongs dramatically diversified during plant evolution, suggesting expanded secretory trafficking systems in plants.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two versions of the 35S promoter that are used in Marchantia: p5-35S 16,47 and p5-35Sx2 20 . Both of them have a strong activity in all parts of the gemmae and thallus except the notch area, where its activity is weak, and the oil body cells, where it is not active 48 (Figure 5B, 6C). On the other hand, the MpEF1α promoter is expressed in all parts of the thallus, but it is especially strong at the notch area 46 (Figure 5C, 6D).…”
Section: Synthetic Promoters For Nuclear Genome Transformationmentioning
confidence: 99%